EFFECTS OF CONDITIONS IN TERMS TREE SHADING-HYGROMETRIC LUMINOUS ENVIRONMENTS AND INTERNAL AND EXTERNAL BUILDING - Durante, Luciane; Nogueira, Marta Crista de Jesus Albuquerque (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707704 The strategy of shading, in hot climates, is one of the main features of bioclimaticarchitecture. This research was aimed to evaluate the effects of passive strategy of the treeshading term hygrometric conditions and luminous of external and internal environments ofbuildings. The methodology consisted of measuring environmental variables in the open, underthe canopy of trees and inside rooms identical shaded and unshaded. These variables were related to morphological and physiological characteristics of individual trees and found to improve thethermal conditions under the canopy outside and inside the shaded rooms. The attenuation oftemperature under the canopy provided by Oiti and hose were 1.3 and 1.5 ° C respectively. TheOiti of leaf area index of 7.4 m2/m2 and total leaf area of 842.5 m2, shading facade oriented to318, provided internal temperature in the room shaded 1oC lower than the room without shading.The hose, leaf area index of 10.1 m2/m2 and total leaf area of 940.7 m2, shading facade oriented263 º, provided internal temperature in the room shaded 1.4 ° C lower than the room withoutshading. There were losses d natural lighting in rooms under the shaded tree shading Oiti andHose, 48 and 82%, respectively. The results show the meaningful contribution of individual treesas mitigators of external and internal microclimate, highlighting the importance of trees for warmweathercities. Losses of natural lighting can be offset with efficient lighting systems that integratenatural and artificial lighting.